Indapamide retard in complex therapy of patients with chronic heart failure and arterial hypertension - S. N. Tereshchenko (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To investigate indapamide retard effects on clinico-laboratory parameters and clinical course in patients with Functional Class (FC) II-IV chronic heart failure (CHF) and arterial hypertension (AH). Material and methods. The study included 60 patients (33 men and 27 women) with FC II-IV CHF and AH; mean age 65,9±1,7 years. All participants were divided into two groups: Group I (n=30) received standard CHF therapy only, Group II (n=30) received standard CHF therapy plus indapamide retard (1,5 mg/d) for 6 months. The dynamics of CHF FC, blood pressure (BP), laboratory parameters, and adverse effect (AE) prevalence were assessed. Results. Indapamide retard therapy was associated with a significant reduction in CHF FC and improved left ventricular ejection fraction. In controls, the results of the 6-minute walk test increased from 299,4±18,8 to 338,4±32,5 m (р>0,05), while in patients receiving indapamide retard, they increased from 288,7±19,2 to 354,6±22,7 m (р=0,031). Positive dynamics of 24-hour BP monitoring parameters was more manifested in the indapamide retard group. After 6 months, NT-pro-BNP level significantly decreased in Group II, but not in Group I. Indapamide retard therapy was not associated with AE, and renal function or glycemia parameters were not affected. Conclusion. Adding indapamide retard to standard treatment of the patients with CHF and AH demonstrated good antihypertensive effects, improved CHF course, and minimal risk of AE.